Problems and Concerns at the Sheriff’s Office of the National Labor Rela-tions Commission – National Capital Region Arbitration Branch (Nlrc-Ncrab) with the Writ of Execution - Muñoz, Arnold D.; Montes, Christine Joyce V.; Ayaay, John Patrick V.; Vigonte, Florinda G.; Malang, Bernandino P.; Abante, Marmelo V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study aims to address the encountered problems and concerns of the National Labor Relations Commission – National Capital Region Arbitration Branch (NLRC-NCRAB) Sheriffs in implementing the writ of execution. A quantitative and descriptive research approach was used, with a survey questionnaire as the research instrument tool. 29 active sheriffs in the NLRC-NCRAB were the respondents of this study. Findings show that most of the incumbent sheriffs at the NLRC- NCRAB are 51-65 years old, have been in the service for at least 6-10 years, and are college graduates. A substantial number received more or less 11-20 writs of execution in a month; a more significant number satisfied an average of 1-10 writs. It was concluded that among the problems and concerns at the Sheriff’s Office regarding the issuance of the writ is the “non-issuance of the break-open, contempt order, and show-cause order” being the top compared to other raised issues encountered by them (M=3.93). It also reveals that parties' compliance relative to the writ, a predominant calculated mean of 3.86, points to the “no coordination by the prevailing parties with the sheriff assigned to the case” and is considered similarly “serious.” Correlatively, the results reveal that in terms of writ implementation, the “non-provision of bonded warehouse and towing vehicles” exhibited the most rated among the enumerated issues and was interpreted “very serious” problem being encountered by the NLRC-NCRAB Sheriffs with a determined mean average of 4.28.